The oxygen delivery response to acute hypoxia during incremental knee extension exercise differs in active and trained males - Kennedy, M. D.; Warburton, D. E. R.; Boliek, C. A.; Esch, B. T. A.; Scott, J. M.; Haykowsky, M. J. (Dynamic Medicine, 2008)
It is well known that hypoxic exercise in healthy individuals increases limb blood flow, leg oxygen extraction and limb vascular conductance during knee extension exercise. However, the effect of hypoxia on cardiac output, and total vascular conductance is less clear. Furthermore, the oxygen delivery response to hypoxic exercise in well trained individuals is not well known. Therefore our aim was to determine the cardiac output (Doppler echocardiography), vascular conductance, limb blood flow (Doppler echocardiography) and muscle oxygenation response during hypoxic knee extension in normally active and endurance-trained males.